Before Consciousness In Search of the Fundamentals of Mind - Radman, Zdravko (Imprint Academic, 2017)
Without consciousness we would not have the experientially flavoured world we have, but without the non-conscious we would not have it at all; for we would not be able to breathe, eat, move, walk, feel, mimic, gesture, laugh, etc., and even see, talk, remember, reason, understand, think, imagine, and make myriad spontaneous decisions as we continuously do in all life situations, from trivial to existential ones. Without consciousness we would not be the kind of creatures we are, but what makes us really unique is our specific non-conscious constellation - a basis from which all mentality germinates and which is irreducible, that is, not representable or in any way simulable. This collection of essays by leading scholars in consciousness aims to show that in order to understand mind as a whole we have to also consider its non-conscious part. Obtaining a more thorough insight into the non-conscious is indispensable for a better understanding of consciousness - consciousness and the non-conscious are to be perceived not as separated but rather as interconnected. The non-conscious is habitually associated with automatized motor behaviour, skills, and habits, but even in their most elementary forms these aspects of mind require a high level of sophistication and cognitive competence. Most complex cognitive tasks, such as perception, memory, decision making, etc. also rely heavily on non-conscious processing, which is not only faster but also proves to be in many respects more fundamental. The investigations included in this volume point to the conclusion that we can behave in a cognitively competent way without recourse to consciousness; that we may act in a reasoned manner even away from awareness; that thinking can be instantiated without engaging the sober conscious reasoner; that our coping in the world is meaningful and fulfilling even when conscious control and volition are dormant. This book aims to integrate the non-conscious as a constitutive dimension of the mind and also to outline how it is indispensable in virtually everything we do.